Information Brokerage Skills: a Necessity in the Digital Library Environment - Chika Jacinta Chinemerem (PT. Pusmedia Group Indonesia, 2024)
As digital technologies continue to revolutionize the information landscape, the role of information professionals has evolved significantly. In the digital library environment, information brokerage skills have become a necessity to bridge the gap between users and the vast amount of digital information available. This seminar explores the critical role of information brokerage skills in digital libraries, emphasizing their importance in information retrieval, evaluation, curation, user support, and information literacy instruction. It also examines the challenges and opportunities presented by the digital age and discusses how information professionals can leverage their expertise to enhance the digital library experience for users. By embracing the challenges and opportunities of the digital age, information brokers play a pivotal role in shaping the future of digital libraries and promoting information literacy in the digital era. In conclusion, information brokerage skills are indispensable in the digital library environment. Information professionals, equipped with information retrieval expertise, curation abilities, and information literacy instruction, enhance the digital library experience and empower users in navigating the digital information landscape